differentiate

Asked by  | 10th Oct, 2009, 05:05: PM

Expert Answer:

A(x) = (r+x)(r2-x2)1/2 = uv where u = (r+x), v = (r2-x2)1/2

dA(x)/dx = d(uv)/dx = udv/dx + vdu/dx ..................using the product rule.

du/dx = 1, and dv/dx = (1/2)(r2-x2)-1/2(-2x)....................using the differentiation rules..chain rule.

Substituting these, the first derivative is,

dA(x)/dx = (r+x)(1/2)(r2-x2)-1/2(-2x) + (r2-x2)1/2

dA(x)/dx = (r+x)(r2-x2)-1/2(-x) + (r2-x2)1/2

Regards,

Team,

TopperLearning.

Answered by  | 11th Oct, 2009, 11:55: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.